Recent Survey on Automatic Ontology Learning - Manimala, R; MuthuLakshmi, G (International Journal of Computer Sciences and Engineering, 2025)
Semantic Web allows machine to understand the data, for that machine-readable semantic metadata is needed.Intelligence is necessary for the creation and processing of semantic metadata. Ontologies play an important role to implement the idea of the semantic web. Ontology is about the exact description of things and their relationships to represent the knowledge. Nowadays Automatic annotation based on artificial intelligence is required for gathering such knowledge. Manual ontology construction is labour-intensive, error-prone process, inflexible, expensive, time consuming and complex task. Ontology Generation or ontology learning includes the automatic extraction of domain‟s terms and the relationships between the concepts from a corpus of text, and encoding them with an ontology language for easy information retrieval. Automatic Ontology generation and sharing it through the web make the web content more accessible to machine. Ontologies can be automatically extracted using various techniques. This paper describes the survey about automatic ontology extraction techniques and various methods used to extract the ontology